2018
DOI: 10.1186/s12943-017-0753-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-494 promotes cancer progression and targets adenomatous polyposis coli in colorectal cancer

Abstract: BackgroundAberrant activation of the Wnt/β-catenin signaling pathway is frequently observed in colorectal cancer (CRC). β-catenin is the major Wnt signaling pathway effector and inactivation of adenomatous polyposis coli (APC) results in nuclear accumulation of β-catenin. It has been suggested that inactivation of APC plays an important role in activation of the Wnt/β-catenin pathway and in the progression of colorectal tumorigenesis. However, the mechanism through which APC mediates colorectal tumorigenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
303
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(307 citation statements)
references
References 44 publications
4
303
0
Order By: Relevance
“…Taken together, the results of the present study suggested that miR494 acts as an oncogene in glioma. Zhang et al (16) reported that microRNA-494 promotes colorectal, epithelial ovarian (17) and pancreatic cancer (18). These results are in line with those of the present study and demonstrated that miR-494 participates in the development and progression of glioma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, the results of the present study suggested that miR494 acts as an oncogene in glioma. Zhang et al (16) reported that microRNA-494 promotes colorectal, epithelial ovarian (17) and pancreatic cancer (18). These results are in line with those of the present study and demonstrated that miR-494 participates in the development and progression of glioma.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, PI3K and Akt may be effective targets for the clinical treatment of glioma cancer (15). Zhang et al (16) reported that miRNA-494 promotes colorectal (16), epithelial ovarian (17) and pancreatic cancer (18). The aim of the present study was to analyze the possible association between microRNA-494 and cell proliferation in glioma.…”
Section: Microrna-494 Promotes the Proliferation And Migration Of Hummentioning
confidence: 89%
“…Subsequently, the β‐catenin will be release from the complex, which induces the accumulation of β‐catenin in cytoplasm. Then, β‐catenin translocates from cytoplasm to nucleolus, where β‐catenin is able to form a complex with the T‐cell factor/lymphoid enhancer factor binding factor (TCF/LEF) transcription factors and results in the transcription of Wnt target genes, such as c‐Myc and CCND1 , which enhances cell proliferation and tumorigenesis (Morin et al, ; Liu et al, ; Zhang et al, ). However, the detailed mechanisms by which the Wnt/β‐catenin is activated in CRC are not fully known.…”
Section: Introductionmentioning
confidence: 99%
“…While miRs have a recognized role in liver disease (50), our studies are the first to show the ER stress reducing activity of miR-494 in the context of liver disease (NASH). miR-494 is known to be oncogenic and drives tumor progression and drug resistance in specific cancer types including colorectal cancer (51) and hepatocellular carcinoma (52,53). Furthermore, miR-494 has been shown to attenuate ischemia reperfusion injury in the liver by regulating the PI3K/Akt signaling pathway (54).…”
Section: Our Data From Gain-and Loss-of-function Experiments Show Thamentioning
confidence: 99%